(untitled) (ASEAN Legal Insights, 2024)
This study delves into the crucial relationship between products and their geographical origins, aiming to enhance consumer trust and promote market differentiation, with a particular focus on Malaysia and Indonesia as case studies. The study investigates the current protective measures for Geographical Indications (GIs) in these countries, highlighting existing issues in their legislation. Additionally, it seeks to identify avenues for possible improving the legal frameworks by drawing on shared experiences. To thoroughly explore these aspects, an extensive literature review was conducted, analysing key international agreements, including the Trade-Related Aspects of Intellectual Property Rights (TRIPs) Agreement and the Paris Convention, alongside relevant national laws governing GIs. Employing a comparative legal analysis, the research assesses the effectiveness of existing legal frameworks, enforcement mechanisms, and the economic implications of GIs in both nations. The findings reveal that GIs significantly could enhance product value, boost market competitiveness, and promote rural development. However, the study also uncovers possible challenges, including issues in legal protections, ineffective enforcement, and the necessity for improved regulatory structures. Drawing from these insights, several key recommendations are proposed to strengthen GI legislation in Malaysia and Indonesia. These include enhancing enforcement mechanisms, establishing effective redress systems for GI infringements, and increasing awareness among producers and consumers regarding the significance and benefits of GIs. Ultimately, this research offers essential insights into how GIs can serve as instruments for economic growth and cultural preservation while addressing the legislative gaps that hinder their potential in Malaysia and Indonesia.